Contextual-Based Shorof Textbook Development for Students of Madrasah Aliyah - Aini, Siti Nurul (Islamic Faculty of KH. A. Wahab Hasbullah University, Jombang, Indonesia, 2024)
The purpose of this study is to describe the Development, Feasibility, and Effectiveness of Contextual-Based Shorof Textbooks. This research employs the Research and Development (R&D) method using the ADDIE model. The results of the research and development are as follows: (1) The Contextual-Based Shorof Textbook developed has dimensions of 18x25 cm and uses Standard Arabic (Fusha). This teaching material consists of 5 chapters containing detailed and comprehensive Shorof material. Each chapter is equipped with explanations, elaborations of the material, and exercises for students in the first and second semesters. (2) Based on the results of validation tests by material expert lecturers, the textbook achieved a score of 125, categorized as valid in terms of material presentation. Meanwhile, the validation test by design expert lecturers scored 134, categorized as highly valid. The validation test by Shorof subject teachers obtained a score of 89, also categorized as highly valid. The effectiveness of the textbook was evaluated using the Paired Sample T-Test. The results showed a significant difference between pre-test and post-test scores, with the t-test significance value greater than the t-table value. This indicates that the Shorof textbook is effective in meeting the needs of students and teachers in teaching and learning Shorof. The implications of this study are that the Contextual-Based Shorof Textbook can serve as a reference for developing similar teaching materials that align with the learning needs at the Madrasah Aliyah level, as well as promote a deeper and more structured understanding of Shorof among students.